Multifunctional polyimides containing triarylamine for electrochromic flexible device, photodetector and resistance memory device. Issue 3 (31st August 2021) - Gao, Yanyu; Zhai, Minghao; Sui, Yan; Li, Dongxu; Lin, Xiaoxue; Pan, Shijia; Pan, Qingjiang; Niu, Haijun; Wang, Wen
Abstract: Integrating different functions in one material will decrease the volume, responding time, and price of device. Polyimides (PIs) are the optimal candidates because of excellent flexible mechanics, thermal stability, and transparent properties. In this work, a series of multifunctional flexible PIs were designed and synthesized from a novel functional triarylamine for electrochromic (EC) device. The PIs show promising application in EC with the efficiency of 205 cm 2 C −1, memory devices with the ON/OFF ratio of 3.7 × 10 4, and photodetectors with a limit being of 0.07 V. Furthermore, the flexible EC device of PI-3 (short for PI 3 made of 4, 4′-(hexafluoroisopropylidene) diphthalic anhydride) keeps excellent stability, and the optical contrast does not decrease even after 2000 cycles.